2022
DOI: 10.1186/s12967-022-03570-w
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles of interleukin-33 in cognitive function by regulating central nervous system inflammation

Abstract: With the advent of an aging society, the incidence of dementia is increasing, resulting in a vast burden on society. It is increasingly acknowledged that neuroinflammation is implicated in various neurological diseases with cognitive dysfunction such as Alzheimer’s disease, multiple sclerosis, ischemic stroke, traumatic brain injury, and central nervous system infections. As an important neuroinflammatory factor, interleukin-33 (IL-33) is highly expressed in various tissues and cells in the mammalian brain, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 157 publications
1
24
0
Order By: Relevance
“…IL‐27 typically produced by antigen‐presenting cells (APCs) can decrease EAE severity through a variety of processes, such as diminishing Th17 cell differentiation and enhancing the production of IL‐10 12,13 . In other anti‐inflammatory cytokines, IL‐33 treatment may have a positive effect on the EAE treatment process by switching from predominantly Th1/Th17 pathogenic cells to Th2 and Treg cells 14 . IL‐35 is another suppressor cytokine mainly released by Treg cells that are required for the maximum inhibitory effect of mouse Treg cells in vitro and in vivo 15 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL‐27 typically produced by antigen‐presenting cells (APCs) can decrease EAE severity through a variety of processes, such as diminishing Th17 cell differentiation and enhancing the production of IL‐10 12,13 . In other anti‐inflammatory cytokines, IL‐33 treatment may have a positive effect on the EAE treatment process by switching from predominantly Th1/Th17 pathogenic cells to Th2 and Treg cells 14 . IL‐35 is another suppressor cytokine mainly released by Treg cells that are required for the maximum inhibitory effect of mouse Treg cells in vitro and in vivo 15 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 In other anti-inflammatory cytokines, IL-33 treatment may have a positive effect on the EAE treatment process by switching from predominantly Th1/ Th17 pathogenic cells to Th2 and Treg cells. 14 IL-35 is another suppressor cytokine mainly released by Treg cells that are required for the maximum inhibitory effect of mouse Treg cells in vitro and in vivo. 15 To date, a variety of anti-inflammatory and immunoregulatory therapies are used to prevent the progress of MS, but they are only several partially effective treatments to modify the disease course.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-33 plays a key role in learning and memory via regulating hippocampal inflammation and synaptic plasticity [ 24 ], but the underlying molecular and cellular mechanisms in dNCR remain unclear. Our study showed that surgery/anesthesia induced postoperative cognitive impairment accompanied by decreased astrocyte-derived IL-33 in aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…IL-33 has been shown to affect cognitive function by modulating neuroinflammation, synaptic plasticity, apoptosis and autophagy [ 24 ]. Numerous studies have shown that the overactivation of microglia and the release of inflammatory factors (e.g., TNF-α, IL-1β, IL-6 and IL-10) induce the occurrence of dNCR by impairing neuronal function [ 20 , 32 ].…”
Section: Discussionmentioning
confidence: 99%